Comparing Survival Outcomes between Hemodialysis and Hemodiafiltration Using Real-World Data from Brazil - da Rocha, Erica Pires; Kojima, Christiane Akemi; Modelli de Andrade, Luis Gustavo [UNESP]; Costa, Daniel Monte; Magalhaes, Andrea Olivares; Rocha, Whelington Figueiredo; de Vasconcelos Junior, Leonardo Nunes; Rosa, Maria Gabriela; Wagner Martins, Carolina Steller (MDPI, 2024)
The CONVINCE trial demonstrates that high-dose hemodiafiltration offers a survival advantage for patients in the high-flux hemodiafiltration group compared to hemodialysis. We compared the outcomes of hemodialysis and hemodiafiltration using real-world data. We conducted an analysis on a cohort of patients who underwent hemodiafiltration therapy (HDF) at a single center, NefroStar Clinics. The results obtained were then compared with data from patients receiving hemodialysis (HD) therapy within the Brazilian Public Health System (SUS). The primary outcome was mortality from any cause. Results: A total of 85 patients undergoing hemodiafiltration were compared with 149,372 patients receiving hemodialysis through the Brazilian Public Health System (SUS). Using a 2:1 propensity score, we compared the 170 best-match HD patients with 85 HDF patients. In the Cox analysis, HDF therapy showed a reduced risk of mortality with an HR of 0.29 [0.11–0.77]. The propensity score analysis showed a HR of 0.32 [95% CI: 0.11–0.91]. This analysis was adjusted for age, type of access, KT/v, hemoglobin, and phosphorus. The Kaplan–Meier analysis showed respective survival rates for HDF and HD at the end of one year, 92.1% and 79.9%, p < 0.001. These results suggest high-flux hemodiafiltration has survival advantages over hemodialysis in a real-world scenario.
Keywords: chronic; hemodiafiltration; kidney failure; real word data; renal dialysis; treatment outcome